Aktivitas Promosi Wisata Kuliner Ikan Bilih Sebagai Makanan Khas Danau Singkarak Kabupaten Tanah Datar - faizah, Salsabila; Edlina, Ria (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
The problem studied in this research is culinary tourism promotion activities for bilih fish as a typical food of Lake Singkarak in promoting and marketing bilih fish culinary tourism. Based on these problems, this research aims to describe the marketing promotion activities used by UMKMactors at the Tourism Department in carrying out promotional activities for the Ikan Bilih culinary tourism product. The research approach used is descriptive qualitative. The source of research data is the result of observations of the activities of the Tanah Datar Regency Tourism Office and UMKM actors at Lake Singkarak. Data collection was carried out using observation, interviews and documentation techniques. The theory used is IMC (integrated marketing communications). This theory was put forward to show that the Bilih Fish culinary tourism promotional activities used by Bilih Fish traders in marketing their tourism products are advertising techniques, sales promotions, personal sales "face to face sales", public relations "public relations" Based on the presentation of results based on data and also the results of interviews conducted by researchers, it was concluded that promotional activities for culinary tourism of bilih fish as a typical food of Lake Singkarak, Tanah Datar Regency, it could be concluded that the five promotional communication indicators implemented by UMKM in Lake Singkarak were based on promotion theory. The mix is ​​advertising (public relations), direct marketing (direct marketing), sales (sales promotion), and personal sales (personal sales) fifth in terms of promotions carried out to increase sales of Bilih Fish in Lake Singkarak. Of the fifth indicators, the least dominant among UMKM actors is advertising, in other words there is still a lack of innovation and creativity in promoting it, not all Ikan Bilih MSME actors in Lake Singkarak are able to market Ikan Bilih culinary delights as creatively as possible. The lack of unity between UMKM in terms of pricing also has an impact on sales of Bilih Fish. The role of the Creative Economy Tourism Office is to provide guidance, facilities and financial support to UMKM.